If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+24=9x+-27
We move all terms to the left:
5x+24-(9x+-27)=0
We add all the numbers together, and all the variables
5x-(9x-27)+24=0
We get rid of parentheses
5x-9x+27+24=0
We add all the numbers together, and all the variables
-4x+51=0
We move all terms containing x to the left, all other terms to the right
-4x=-51
x=-51/-4
x=12+3/4
| -8(0.5y–3)=3 | | 2. -3y–5=10 | | 4x=948 | | 35π/6=7.2x | | 5x+7=15-x | | -15x–4+6x=-4–9x | | 2-4x-3x=1 | | 63x=16x^2-16x+20x-20 | | k–9=-3 | | 3x^{2}+12x=2x+8 | | k–9=–3 | | 360/k=8 | | 6-20x+6x^2=0 | | 3x=648 | | 6+-20x+6x^2=0 | | u/3+16=43 | | 4(x-2)-3=11x.x-1 | | -1+7u=-9(-2u+5) | | 3/8a-a/12+7/2=7 | | 2d+12=46 | | (1/2)a-(1/2)=-4 | | 2s=-3s-5(-2s-9) | | P=10/6(c)4/12 | | 3/8a-9/12+7/2=7 | | 158-x=64 | | i-98,674=157,640 | | 4x+4=(7x-9) | | 2.3j+4(0.7j+2.77)=7(0.7j+2.36) | | 10b-20=10+20b | | 10x+63=5x–3 | | 4(21-x)+2x=68 | | 7s=7+7(2s-9) |